1991
DOI: 10.1088/0957-0233/2/4/012
|View full text |Cite
|
Sign up to set email alerts
|

A solid-state switched small TEA CO2laser

Abstract: A corona pre-ionized, solid-state switched transverse, electric, atmospheric CO2 laser has been developed. This small aperture, low repetition rate laser can produce 114 mJ optical pulses from a discharge volume of 15.6 cm3, with an energy efficiency of 12.7%. The device is driven by a simple inexpensive solid-state exciter, which uses a series stack of thyristors, to provide an output efficiency similar to that produced by a conventional thyratron circuit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Here, the laser is operated by switch in the primary part of the pulser which handles much lower voltages, longer pulses and smaller energies. The successful operation of pulser sustainer TEA-CO 2 laser (Taylor & Lepold 1985Sylvan et al 1991) and excimer laser (Timmeraans et al 1993) using ASSE has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the laser is operated by switch in the primary part of the pulser which handles much lower voltages, longer pulses and smaller energies. The successful operation of pulser sustainer TEA-CO 2 laser (Taylor & Lepold 1985Sylvan et al 1991) and excimer laser (Timmeraans et al 1993) using ASSE has been reported.…”
Section: Introductionmentioning
confidence: 99%